A new classification of genus Neoperla and systematic studies of other Perlinae (Plecoptera: Perlidae) - Zwick, Peter (Zootaxa, 2023)
A new formal classification for the largest genus of Perlinae, Neoperla, is introduced to replace the artificial split of the genus into two informal groups. Globally, there are close to 300 named species, with the number rising all the time. The monophyletic clymene-group is assigned to Neoperla (Neoperla) with ~ 140 species in North America, Africa and parts of Asia; its seven main subgroups are briefly characterized. The polyphyletic Asian montivaga-group is replaced by two monophyletic subgenera, N. (Borneella), new subgenus (six species), and N. (Formosita) Klapálek, new status (~125 species). Five species groups in N. (Formosita) are recognized and diagnosed. For 85% of the species known by mid-2023 (DeWalt et al. 2023), their assignment to supra-specific taxa is summarized in a table, while a further 40 species cannot be placed at present. Some additions, remarks and corrections to the phylogenetically oriented synopsis of Perlinae by Sivec, Stark & Uchida (1988) are made. The new species N.(F.) fasciata is named. Eighty-eight figures, including numerous new original photographs, are presented.